Avaliação do currículo do curso de Ciências Contábeis de uma Instituição de Ensino Superior Federal sob as perspectivas Andragógica e Heutagógica - Del Sent, Edegar Luiz (2023)
This study aimed to analyze the perception of teachers and students in the Accounting Sciences course at a higher education institution (HEI) regarding the alignment of the actual curriculum with the pillars of andragogy and heutagogy. A qualitative quantitative approach and a single case study strategy were followed to collect information from documentary sources and the perceptions of teachers and students through questionnaires, interviews, and focus groups. Data analysis was guided by Yin's (2014) case study protocol and Bardin's (1977) data analysis. The research participants were students and faculty members of the Accounting Sciences course at the Federal Technological University of Paraná, Pato Branco campus (UTFPR). The results showed that the majority of students and teachers agree that the course meets its proposed objectives, but there are divergences regarding the flexibility of the curriculum structure and the production of scientific research. Analyzing the alignment of the actual curriculum with the pillars of andragogy and heutagogy, it was identified that andragogical practices prevail in various aspects, such as principles, curricular model, student practice, reasons for learning, motivation, student experiences, and willingness to learn. However, only the teachers' perception identified heutagogical characteristics in the teacher-student relationship category. Furthermore, a mixture of andragogical and heutagogical perceptions was observed among students in the categories of teacher-student relationship and learning orientation. The results indicate that students perceive a heutagogical approach in the teaching practices, while teachers have a heutagogical perception in the teacher-student relationship. It can be concluded that although andragogical practices prevail, there is a clear trend towards a heutagogical approach, in which the student plays a more active role and the teacher assumes the facilitator role. This trend should be considered by educational institutions to improve their practices and make academic education more suitable for the needs of students and the job market